Cognitive Processes in Criminal Profile Construction: A Preliminary Study - Kocsis, Richard N. (International journal of offender therapy and comparative criminology, 2005)
This study undertook an empirically based examination of the cognitive processes associated with the accurate construction of a criminal psychological profile. This was accomplished by comparing the abilities of profilers and nonprofilers in two simulated profiling exercises that measured both profile accuracy and an individual's performance on various tests of memory and comprehension related to the case materials presented in each exercise. The results of these experiments suggest that an incremental relationship exists between comprehension of the case materials and accuracy of the profiles generated. In addition, the findings provide some tentative indications that the comprehension of case material in a narrative (i.e., written) format is an integral cognitive function to proficient profiling